#KaburAjaDulu: A Digital Manifestation of Indonesian Youth’s Response to Societal and Structural Crises - Ardianti, Ruth; Yunita Monique, Putri; Rahman Eka, Agus; Handayani Saharuddin, Sri; Latifah, Humairah (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the digital phenomenon of the hashtag #KaburAjaDulu ("just escape first") as a symbolic expression of Indonesian youth responding to structural pressures and social crises. Behind its seemingly humorous tone, this hashtag encapsulates deeper narratives of dissatisfaction with economic stagnation, distrust in state institutions, and widespread psychological exhaustion. The research employs a qualitative approach with a phenomenological design to explore the lived meanings embedded in these digital expressions. Data were collected through digital ethnographic observation and purposive sampling of 150 social media posts using the hashtag, sourced from Twitter, TikTok, and Instagram between 2023 and 2025. The data were analyzed thematically, supported by visualizations of digital narrative distribution. Findings suggest that the hashtag serves as a symbolic escape from perceived structural stagnation, while also acting as a subtle medium of protest. Dominant themes include individual economic hardship, loss of trust in public institutions, and aspirations to seek a better life abroad. Users often express their frustrations using humor, irony, and memes, demonstrating that digital culture provides not only an outlet for emotional release but also a channel for soft resistance. This study contributes to the growing literature on affective digital activism by showing how symbolic, emotionally charged expressions can reflect more profound social discontent. It also urges policymakers to recognize these online narratives as meaningful signals of youth sentiment. Future research should explore cross-platform expressions and the algorithmic dynamics behind the spread of such digital discourse in an increasingly mediated society.